Study of the electrical parameters degradation of GaAs sub-cells for triple junction space solar cells by computer simulation - Cappelletti, Marcelo Ángel (2016)
In this paper, a theoretical study of the electrical parameters degradation of different n-type GaAs sub-cells for InGaP/GaAs/Ge triple junction solar cells irradiated with 1 and 5 MeV electrons has been performed by means of computer simulation. Effects of base carrier concentration upon the maximum power point, short-circuit current, open circuit voltage, diffusion current, recombination current and series resistance of these devices have been researched using the displacement damage dose method, the one-dimensional PC1D device modeling program and a home-made numerical code based on genetic algorithms. The radiative recombination lifetime, damage constant for minority-carrier lifetime and carrier removal rate models for GaAs sub-cells have been used in the simulations. An analytical model has been proposed, which is useful to describe the radiation-induced degradation of diffusion current, recombination current and series resistance. Results obtained in this work can be used to predict the radiation resistance of solar cells over a wide range of energies.